(untitled) (Singaporean Journal of Business Economics and Management, 2018)
Social responsibility of business entities is the great challenge for this century. Many big companies and organizations are grabbing huge profits from the local market without identifying the sustainable practices and ignoring the international standards for product manufacturing. This article was set out to assess the practice of corporate social responsibility (CSR) and its relationship on organization perceived performance: case of Ethiopian manufacturing firms. Primary data were collected from 121 Ethiopian manufacturing firms. The respondents were assessed on major area of corporate social responsibilities. Both Descriptive analysis and Spearman Correlation were used for assessing the Practice of CSR and measuring its relationship with perceived performance of the manufacturing firms. Data analysis using SPSS revealed that CSR is a familiar concept in the sector as most of the manufacturing firms engage in CSR activities. At the same time, the major areas of focus of the CSR includes Protecting the environment, Waste management, building open area (statues), Funding the needy people in case of emergency, establishing sport team, Funding children’s education, assisting the development projects of the country and sponsoring many social events and others. The results of correlation indicated a significant relationship between CSR practices and perceived performance of the manufacturing firms and perceived performance.